From supermodernism to neotraditionality: the contemporary search for Latin American architectural identity - Arnet-Callealta, Virginia (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
The purpose of this article is to demonstrate that there is a Latin American condition of contemporary architecture. Therefore, it focuses on the detailed analysis of the epistemological scope of Latin America to subsequently define the essential aspects and arguments in its territory and its architecture. Furthermore, the methodological approach allows establishing identity parameters such as the landscape in Chile, tropicalism in Brazil, the mix of cultures in Mexico, the material in Colombia or the brick in Argentina and Paraguay, which contributes to the determination of Latin American architecture from the global perspective. Finally, the discussions and reflections at the end of the process confirm the relevant role of the development of local identities within the complex global panorama thanks to the understanding of a common Latin American condition.